Bluetongue and footrot outbreaks in migratory Sheep due to unseasonal rains/ floods: Special reference to BTV Serotype 12 - CHANDRANAIK, B M; MAYACHARI, MANJUNATHA; NAGARAJA, K; GOMES, AMITHA REENA; RIZWAN, APSANA; ALAMELU, M S; BYREGOWDA, S M (The Indian Journal of Animal Sciences, 2023)
Following heavy rains and floods during October-November of 2019, outbreaks of Bluetongue (BT) disease was witnessed in migratory sheep in flood affected areas. The disease was investigated in fifteen migratory flocks in Karnataka state, involving a total of 3575 sheep with over 1480 ailing and 428 deaths. Samples collected from 208 ailing and 79 dead animals were initially subjected for NS1 genome based group specific Bluetongue virus (BTV) detection by Reverse Transcription-PCR (RT-PCR) and later for segment 2 genome based serotype specific RTPCR. The RT-PCR and phylogenetic analysis confirmed the virus involved in the current outbreak as BTV serotype 12. This data gives further insights into BT epidemiology and recommends inclusion of locally circulating BTV serotype/s in vaccines in endemic regions for effective control of BT. Since these migratory sheep were forced to stand in water stagnated agricultural fields/lands for days to weeks due to continuous rains, they were concurrently affected with acute footrot caused by Fusobacterium necrophorum and Staphylococcus aureus. Foot-tanks and higher antibiotics were very effective in treatment of footrot in the current outbreak. Present study is an evidence of how unforeseen natural calamities can disrupt animal health with profound socio-economic consequences eventually affecting the food-chain and here a few scientific measures have been attempted to mitigate such animal health crisis.